Five-Year Outcomes With Pembrolizumab Versus Chemotherapy for Metastatic Non–Small-Cell Lung Cancer With PD-L1 Tumor Proportion Score ≥ 50%. Issue 21 (20th July 2021) - Reck, Martin; Rodríguez-Abreu, Delvys; Robinson, Andrew G.; Hui, Rina; Csőszi, Tibor; Fülöp, Andrea; Gottfried, Maya; Peled, Nir; Tafreshi, Ali; Cuffe, Sinead; O'Brien, Mary; Rao, Suman; et al.
Abstract : PURPOSE: We report the first 5-year follow-up of any first-line phase III immunotherapy trial for non–small-cell lung cancer (NSCLC). KEYNOTE-024 (ClinicalTrials.gov identifier: NCT02142738 ) is an open-label, randomized controlled trial of pembrolizumab compared with platinum-based chemotherapy in patients with previously untreated NSCLC with a programmed death ligand-1 (PD-L1) tumor proportion score of at least 50% and no sensitizing EGFR or ALK alterations. Previous analyses showed pembrolizumab significantly improved progression-free survival and overall survival (OS). METHODS: Eligible patients were randomly assigned (1:1) to pembrolizumab (200 mg once every 3 weeks for up to 35 cycles) or platinum-based chemotherapy. Patients in the chemotherapy group with progressive disease could cross over to pembrolizumab. The primary end point was progression-free survival; OS was a secondary end point. RESULTS: Three hundred five patients were randomly assigned: 154 to pembrolizumab and 151 to chemotherapy. Median (range) time from randomization to data cutoff (June 1, 2020) was 59.9 (55.1-68.4) months. Among patients initially assigned to chemotherapy, 99 received subsequent anti–PD-1 or PD-L1 therapy, representing a 66.0% effective crossover rate. Median OS was 26.3 months (95% CI, 18.3 to 40.4) for pembrolizumab and 13.4 months (9.4-18.3) for chemotherapy (hazard ratio, 0.62; 95% CI, 0.48 to 0.81). Kaplan-Meier estimates of the 5-year OS rate were 31.9% for the pembrolizumab group and 16.3% for the chemotherapy group. Thirty-nine patients received 35 cycles (ie, approximately 2 years) of pembrolizumab, 82.1% of whom were still alive at data cutoff (approximately 5 years). Toxicity did not increase with longer treatment exposure. CONCLUSION: Pembrolizumab provides a durable, clinically meaningful long-term OS benefit versus chemotherapy as first-line therapy for metastatic NSCLC with PD-L1 tumor proportion score of at least 50%.